2015
DOI: 10.1186/s13048-015-0186-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200c and microRNA-31 regulate proliferation, colony formation, migration and invasion in serous ovarian cancer

Abstract: BackgroundSerous epithelial ovarian cancer (SEOC) is a highly metastatic disease and its progression has been implicated with microRNAs. This study aimed to identify the differentially expressed microRNAs in Malaysian patients with SEOC and examine the microRNAs functional roles in SEOC cells.MethodsTwenty-two SEOC and twenty-two normal samples were subjected to miRNA expression profiling using the locked nucleic acid (LNA) quantitative real-time PCR (qPCR). The localization of miR-200c was determined via LNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
2
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 37 publications
5
38
2
2
Order By: Relevance
“…In contrast to epithelial cancer cells where miR-200c expression blocks EMT, proliferation, and metastasis (Gregory et al, 2008;Hur et al, 2013;Ibrahim et al, 2015;Liu et al, 2014;Song et al, 2015;Tang et al, 2013;Yu et al, 2010), our analysis of osteosarcoma tumors indicate a robust correlation between miR-200c expression and metastasis. To further test this novel paradigm, we performed a series of in vitro experiments with U2-OS cells, a human cell line originally derived from a primary osteosarcoma.…”
Section: Exogenous Expression Of Mir-200c In Osteosarcoma Cells Enhancontrasting
confidence: 67%
“…In contrast to epithelial cancer cells where miR-200c expression blocks EMT, proliferation, and metastasis (Gregory et al, 2008;Hur et al, 2013;Ibrahim et al, 2015;Liu et al, 2014;Song et al, 2015;Tang et al, 2013;Yu et al, 2010), our analysis of osteosarcoma tumors indicate a robust correlation between miR-200c expression and metastasis. To further test this novel paradigm, we performed a series of in vitro experiments with U2-OS cells, a human cell line originally derived from a primary osteosarcoma.…”
Section: Exogenous Expression Of Mir-200c In Osteosarcoma Cells Enhancontrasting
confidence: 67%
“…Another validated target of miR-200c is DLC1 (deleted in liver cancer-1), which is a tumor and metastasis suppressor that regulates actin formation and focal adhesion (Feng et al, 2013). In a study on EOC, forced expression of miR-200c reduced DLC1 expression in conjunction with increased cell proliferation and suppression of serous EOC invasion and migration (Ibrahim et al, 2015), consistent with the known role of DLC1 .…”
Section: Mir-200c-mediated Metastasissupporting
confidence: 52%
“…Since miR-122 has been identified as a marker of differentiation [94, 95] it makes sense that this miRNA is decreased in CCA as opposed to PSC. In contrast to miR-122 levels, miR-200c is downregulated in PSC but upregulated in CCA, and previous work has shown that miR-200c increases tumor growth and proliferation [96, 97], helping to explain this discrepancy in expression. Finally, miR-92a, another miRNA that supports tumor growth [98], shows decreased expression in PBC but increased expression in BA.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%